PROJECT BASED LEARNING SEBAGAI SOLUSI MELATIH KETRAMPILAN BERPIKIR KREATIF SISWA SD DALAM PEMBELAJARAN IPS - Fadhilah Dwi Amalia; Fajar Setiawan; Kunti Dian Ayu Afiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This study aims to determine the application of the project-based learning model (PjBL) to train the creative thinking skills of fifth grade students at SD Muhammadiyah 13 in social studies learning. The research method used is qualitative research with a descriptive approach. The data collection technique used is technique and source triangulation. Triangulation techniques include observation, interviews, and documentation. While triangulation of sources includes fifth grade students, fifth grade teachers, and school principals. The results of the research on the application of the PjBL learning model that has been implemented properly in accordance with the PjBL syntax can train students' creative thinking skills, with the application of PjBL students can have the opportunity to train and develop their creative thinking skills, and this PjBL model can train students' creative thinking skills in social studies learning.